Confirmation of the presence of Mycobacterium tuberculosis and other mycobacteria in mycobacterial growth indicator tubes (MGIT) by multiplex strand displacement amplification. - Badak, F Z (1997)
Multiplex strand displacement amplification (mSDA) is capable of amplifying three distinct DNA sequences simultaneously. These include sequences present in most genera of mycobacteria, a sequence specific for Mycobacterium tuberculosis, and an internal control. mSDA was used to detect the presence of these target sequences in 154 (72 positive, 76 negative, and 6 failed) clinical specimens cultured in the mycobacterial growth indicator tube (MGIT) system. A wide variety of specimen types were processed and cultured. Once these cultures were deemed positive by MGIT fluorescence or were deemed negative after 8 weeks of incubation, MGIT culture aliquots were processed for mSDA analyses. A chemiluminescent microwell assay was used to detect the amplified products. The procedure was relatively simple and took less than 6 h to complete. The sensitivity of mSDA for detecting acid-fast bacilli was 96.4% compared to that of MGIT culture. Sensitivity and specificity were 97.2 and 96.1%, respectively, when all clinical criteria were considered. mSDA was shown to be a rapid and effective method for confirming the presence of M. tuberculosis and other mycobacteria in positive MGIT cultures.